Evaluation of National Health Insurance (JKN) Claims at Khidmat Sehat Afiat Hospital, Depok City - Robiatul Adawiyah; R. Sutiawan; Hirty Lianda (Jurnal Publikasi Kesehatan Masyarakat Indonesia, 2023)
The implementation of JKN claims based on previous research shows that there are still several problems. Therefore, it is necessary to evaluate JKN claims at the Khidmat Sehat Afiat Regional Hospital, Depok City. Research objective to find out how JKN claims are evaluated at the hospital. This research method uses qualitative with a case study approach. Data was collected using structured participant observation, document review and interviews. Data sources were obtained from primary data and secondary data. The results of this research are that the trend in the number of JKN claims for inpatient and outpatient visits is fluctuating and there are still pending claims. Evaluation of JKN claims based on a system approach is divided into input components (man, money, method, machines, material), process (complete and appropriate claim form, internal verification and input to the claim application, submission of claims to BPJS Health, issuance of BAHV (Result Minutes). Verification) by BPJS Health, claim payment) and output (accuracy of claim payment). There are several problems with the input component in the form of double jobs, INA CBG costs are lower than the costs incurred by hospitals, SIMRS needs development and problems with the internet network. Meanwhile, obstacles were found in the process components from internal and external factors. Conclusion: that the JKN claim is running well, but there is still a need to make improvements to the problems found.